A case of sebaceous carcinoma in the eyelid: The results of chemoradiotherapy after recurrence - Şirin Özdemir, Beyza; İlhan, Hatice Deniz and Korcum, Aylin and Genç, Mine (Journal of Surgery and Medicine, 2020)
Sebaceous carcinoma of the eyelid, a rare and locally aggressive malignant neoplasm, can metastasize via the lymphatic and hematogenous route. The diagnosis and treatment can be delayed because of the similarity of the tumors with benign lesions. We herein present a 65-year-old male patient who was diagnosed with sebaceous carcinoma of the left upper eyelid 7 years ago, after which surgical resection was performed. Regional recurrence developed in left cervical nodes two years later. Left neck dissection was performed and adjuvant radiotherapy was administered. The patient has no evidence of recurrence or metastasis after radiotherapy during 5 years of follow-up.